2017
DOI: 10.1590/0103-8478cr20160595
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fractions in soil after successive crops of Pinus taeda L. without fertilization

Abstract: Pinus cultivation without fertilization is a common practice in southern Brazil, which can induce a decline in the availability of phosphorus (P) in the soil. The purpose of this study was to evaluate the changes in phosphorus fractions in a Humic Cambisol subjected to continuous Pinus taeda L. cultivation without fertilization. Two forest stands were evaluated, after 16 years of Pinus cultivation (1st crop) and 49 years (3rd crop), when soil samples were collected (layers 0-10, 10-20, 20-40, 40-60, and 60-80c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In assessing the role of soil P fractions to tree nutrition in a short-term experiment, Niederberger et al (2017) found poplar trees to decrease readily and moderately labile P fractions, thus showing the importance of these fractions in tree nutrition. It has also been shown that pine, eucalyptus and cypress trees decrease organic P content and, utilize even non-labile P due to enhanced enzymatic activities, mycorrhizal associations as well as changes in soil pH, which enhances P mineralization (Chen et al, 2008;Gatiboni et al, 2017). Phosphorus is mainly recycled into the soil through litterfall in forests (Qiong et al, 2008) hence litter input and quality greatly influence P concentration in forest soils.…”
Section: Changes In Soil P Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In assessing the role of soil P fractions to tree nutrition in a short-term experiment, Niederberger et al (2017) found poplar trees to decrease readily and moderately labile P fractions, thus showing the importance of these fractions in tree nutrition. It has also been shown that pine, eucalyptus and cypress trees decrease organic P content and, utilize even non-labile P due to enhanced enzymatic activities, mycorrhizal associations as well as changes in soil pH, which enhances P mineralization (Chen et al, 2008;Gatiboni et al, 2017). Phosphorus is mainly recycled into the soil through litterfall in forests (Qiong et al, 2008) hence litter input and quality greatly influence P concentration in forest soils.…”
Section: Changes In Soil P Fractionsmentioning
confidence: 99%
“…However, the tendency to exploit more forest lands to increase the overall agricultural production could have negative effects on soil fertility and biodiversity due to alteration of soil properties and reduction in soil organic matter content (de Graaff et al, 2019;Tolimir et al, 2020). Reduction in soil organic matter content, for instance, causes a collapse in soil structure and a weakening of soils' capacity to retain nutrients (Qiong et al, 2008;Gatiboni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have evaluated responses to management practices using improved genetic material, mechanical site preparation, control of competing vegetation, and fertilization in Pinus plantations, and found positive results in the relationship between productivity and soil chemical attributes, significantly improving the growth of species when best tillage practices were recommended (Albaugh et al 2010, Batista et al 2015. Other studies have reported that successive cycles of Pinus plantations without nutrient replacement tend to cause a nutritional deficit for the trees, resulting in low productivity in forest plantations (Gatiboni et al 2017, Gatiboni et al 2020). Therefore, assessing soil microbiological attributes and their relationships with chemical and physical soil characteristics, combined with site-specific silvicultural management practices in Pinus taeda, provides a better understanding of soil nutrient dynamics (Sixel et al 2015, Tulio et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In southern Spain, on calcareous Vertisols and related Inceptisols, labile P can be predicted in practice using P tests and extractable Fe values [14]. The type of land use and management of P also affect the availability of P. Continuous cultivation of plants on humic cambisol without fertilization can lead to a decrease in the availability of phosphorus (P) in the soil [15]. Land use shift from forest to pasture for extensive pastoralism in the Colombian Amazon resulted in a 31.1% decrease in labile inorganic P fractions, with mineralization of organic P by the enzyme phosphatase playing a significant role in P availability [16].…”
Section: Introductionmentioning
confidence: 99%